Wafer-scale synthesis of defined polymer brushes under ambient conditions. Issue 47 (9th October 2015) - Zhang, Tao; Du, Yunhao; Kalbacova, Jana; Schubel, René; Rodriguez, Raul D.; Chen, Tao; Zahn, Dietrich R. T.; Jordan, Rainer
Abstract : A facile method to synthesize dense, homo- and multiblock copolymer brushes on the wafer-scale under ambient conditions is presented. Abstract : A method is presented that allows for the first time the preparation of highly defined polymer brush coatings on the wafer-scale under ambient conditions (room temperature, exposure to air) from a broad variety of monomers. The discovered high oxygen-tolerance of the surface-initiated Cu(0)-mediated controlled radical polymerization (SI-CuCRP) yields entire wafers homogeneously covered by a polymer brush of linear, high molar mass polymers with narrow dispersities ( Đ = 1.1) at extremely high grafting densities (≈1 chain per nm 2 ). The low-tech and air tolerant method requires only ≲4 mL reaction solution containing a monomer and a ligand between two facing substrates. Thus, the SI-CuCRP is scalable to any surface area with minimal costs and minimal equipment. Despite the simplicity of the method, the high endgroup fidelity of SI-CuCRP is demonstrated by the preparation of a tetrablock copolymer brush which is the first example of a higher order block copolymer brush prepared by any surface-initiated polymerization. Finally, we present a new facile lithographic technique, the copper plate proximity printing (CP 3 ), which relies on the proximity of the bulk copper surface to the initiator-bearing substrate. The CP 3 is resist- and development-free and transfers the copper plate profile (of a copper coin) directly into an image composed of a 3D polymer brush.